Style, rhetoric and creativity in language : in memory of Walter (Bill) Nash (1926-2015) - Simpson, Paul; Nash, Walter (Linguistic approaches to literature, 2019)
"This commemorative volume comprises ten essays which celebrate the work of Walter (Bill) Nash. Bill Nash was an extraordinary scholar--a classicist, parodist, critic, musician, linguist, poet, polyglot, humourist and novelist. He was as adroit in his reading of the Old Norse sagas as he was in his analyses of the rhetorical composition of everyday English usage, and his published outputs embrace the stylistic, rhetorical, compositional and creative topographies of both language and literature. The contributions that comprise this volume are all by well-known scholars in the field and each essay celebrates Nash's prodigious offering by covering the academic fields with which he was particularly associated. These fields include composition, rhetoric, discourse analysis, English usage, comic discourse, creative writing and the stylistic exploration of literature from the Old English period to that of the present day"--